Speech Perception in Noise Predicts Oral Narrative Comprehension in Children With Developmental Language Disorder - Magimairaj, Beula M.; Nagaraj, Naveen K.; Champlin, Craig A.; Thibodeau, Linda K.; Loeb, Diane F.; Gillam, Ronald B. (Frontiers in Psychology, 2021)
We examined the relative contribution of auditory processing abilities (tone perception and speech perception in noise) after controlling for short-term memory capacity and vocabulary, to narrative language comprehension in children with developmental language disorder. Two hundred and sixteen children with developmental language disorder, ages six to nine years (Mean = 7;6), were administered multiple measures. The dependent variable was children’s score on the narrative comprehension scale of the Test of Narrative Language. Predictors were auditory processing abilities, phonological short-term memory capacity, and language (vocabulary) factors, with age, speech perception in quiet, and nonverbal IQ as covariates. Results showed that narrative comprehension positively correlated with the majority of the predictors. Regression analysis suggested that speech perception in noise contributed uniquely to narrative comprehension in children with developmental language disorder, over and above all other predictors, however, tone perception tasks failed to explain unique variance. In conclusion, the relative importance of speech perception in noise over tone-perception measures for language comprehension reinforces the need for the assessment and management of listening in noise deficits and makes a compelling case for the functional implications of complex listening situations for children with developmental language disorder.